LITERARY FICTION AND REPRESENTATION OF HISTORY: GEORGIAN CASE STUDY - Chkhartishvili, Mariam (PEOPLE: International Journal of Social Sciences, 2019)
In the nineteenth century the process of history professionalization took place. It was characterized by exclusive development of the discipline. The “founding fathers” tried to bold the borderlines between the history and other disciplines and sharpen the focus of historical researches. Just this view was reflected in fact of choosing archival data and official documents as only reliable type of sources and also the established view about the honest academic enabling to represent “what actually happened” ̶ formula proposed by L.Ranke. In the twentieth century subject of history was conceptualized in a new way. This was an epoch of so-called “New History” which had introduced interdisciplinary approach in historical research. The new generation of historians developed interest to the topics which in recent past might be treated as not relevant for the academic occupation. In this very context appeared necessity of literary sources’ use. This search for new sources was favoured by the coincidence in time with dispute about historicity of literature. The part of practitioners of history ignored it and preferred to make history in a traditional way, i.e. in spirit of Rankean historiography. This was case at least in Georgia and it continued to be the same in nowadays. The paper aims to fill (of course only partially) this gap in Georgian scholarship. It uses one monument of nineteenth century Georgian literary fiction for reconstructing of reality and elaborates on more general topic concerning the realistic prose as important source for history representation.